2018
DOI: 10.3389/fimmu.2018.01706
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Facilitates Crosstalk Between Endoplasmic Reticulum Stress and IL-6 Release in the Intervertebral Disc

Abstract: Degenerative disc disease is associated with increased expression of pro-inflammatory cytokines in the intervertebral disc (IVD). However, it is not completely clear how inflammation arises in the IVD and which cellular compartments are involved in this process. Recently, the endoplasmic reticulum (ER) has emerged as a possible modulator of inflammation in age-related disorders. In addition, ER stress has been associated with the microenvironment of degenerated IVDs. Therefore, the aim of this study was to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 59 publications
2
27
1
Order By: Relevance
“…Because inflammation may be a key factor in RPE degeneration, dysfunction and loss in retinal degenerative diseases, the intracellular signaling pathways involved in initiating the release of cytokines and chemokines in RPE cells are important. One of the most widely reported signaling pathways in many cell systems is the MAPK signaling pathway, in which inflammatory stimulants contribute to the activation of MAPKs, followed by increased release of cytokines and chemokines [91,92,93]. Quercetin has been reported to have anti-inflammatory effects via inhibiting the activation of MAPKs in a number of different cell lines treated with different inflammatory stimulants [14,34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Because inflammation may be a key factor in RPE degeneration, dysfunction and loss in retinal degenerative diseases, the intracellular signaling pathways involved in initiating the release of cytokines and chemokines in RPE cells are important. One of the most widely reported signaling pathways in many cell systems is the MAPK signaling pathway, in which inflammatory stimulants contribute to the activation of MAPKs, followed by increased release of cytokines and chemokines [91,92,93]. Quercetin has been reported to have anti-inflammatory effects via inhibiting the activation of MAPKs in a number of different cell lines treated with different inflammatory stimulants [14,34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The p38 signaling pathway is generally activated by stressors and is known to regulate inflammation, autophagy, apoptosis, and differentiation [ 241 ]. Numerous studies have investigated p38 in the IVD, thereby identifying hypoxia [ 245 ], hyperosmolarity [ 120 ], hyperphysiological mechanical loads [ 133 ], ER stress [ 258 ], acidity [ 257 ], high glucose levels [ 256 ], and IL-1 [ 253 ] as potent activators. Interestingly, p38 is connected to TPRV4 [ 133 ], which has previously been described to transduce mechanical, inflammatory, and pain signals in cartilage [ 259 ].…”
Section: Ivd Regeneration Strategies: Biological Targets and Biomamentioning
confidence: 99%
“…Interestingly, p38 is connected to TPRV4 [ 133 ], which has previously been described to transduce mechanical, inflammatory, and pain signals in cartilage [ 259 ]. Different research fields have shown extensive cross talk between p38 and other signaling pathways, e.g., ERK [ 258 ], TGF-β/Smad, [ 260 ] or Akt [ 261 ], which should be investigated in IVD cells. Overall, inhibition of p38 is being discussed for therapeutic approaches, potentially reducing inflammation, pain, and disc matrix catabolism [ 253 , 262 ], although ultimate outcomes may be difficult to predict due to the extensive cross talk with other pathways.…”
Section: Ivd Regeneration Strategies: Biological Targets and Biomamentioning
confidence: 99%
“…23 The crosstalk between ER stress and IL-6 release has been reported previously. 24 Krupkova et al showed that IL-6 release was increased following ER stress activation and that the crosstalk between ER stress and IL-6 induction was enhanced by phosphorylation of p38 F I G U R E 5 Effects of 4-phenylbutyric acid (4-PBA) on arthritis severity in collagen-induced arthritis (CIA) mice. (A) Representative front and hind paws of mice of each group, and average paw thickness score and clinical score of CIA mice treated with 4-PBA (240 mg kg −1 day −1 ) or phosphate buffered saline (PBS) (vehicle) (15 mice per group).…”
Section: Discussionmentioning
confidence: 99%